The transgressive individual in Foucault’s rights-punishment theory: a record of self-resistant subjectivity in China - Yuetong, Zhao (Deviant behavior, 2024)
Foucault’s philosophical theories and sociological boundaries are not mutually exclusive, and his idea of "micro-power" breaks through the traditional sociological perspective of power studies to reveal a set of hidden mechanisms of power operation and networks of power relations, as well as an anthropological examination of how to regulate the human physical and mental spheres. In modern society, as sexual minorities, addicts, AIDS patients and criminal ex-convicts are typical marginalized figures under different social types and community governance. Therefore, this paper aims to analyze how individuals become marginalized and excluded in the social order of functioning through the transformative mechanism from punishment to regulation in Foucault’s micro-power, and to reveal how abnormal people, behaviors and phenomena are regulated and implicitly dismembered by the rapidly constructed new social order in China’s transition period through the documentary the two lives of Li Ermao.